Experiences on the Initiation to University Teaching in the Faculty of a Mexican Public Institution - Rodríguez Pech, Juanita de la Cruz (2018)
The analysis of the conditions in which an individual starts a career in university teaching is the departure point of this work, whose core interest is the initiation period. With previous research about work insertion into the education sector as a reference, this paper discusses the relevance of support provided to staff in the initial stages of their work, as an opportunity to equip them with the training they lack. In that sense, the aim of this article was to describe the initiation experiences taking place during the first years of teaching of a group of five professors, with whom semi-structured interviews were carried out. A finding was that the work and training experiences of the professors at the time they started working at the university worked as resources to face the challenges presented by the educational task. In the same way, the direct experience and the models obtained from other professors were important elements that guided their decisions. It can be concluded that the challenges found and the strategies that were developed to face them have been varied in these professors, based on the professional development they have had.